The effect of MOSFET second-order nonlinearity on active inductor-based oscillators - A'ain, Abu Khari; Ler, Chun Lee; Kordesch, Albert Victor (Institute of Electrical and Electronics Engineering (IEEE), 2007)
Second-order nonlinearity of the MOSFET has significant impact on active inductor (AI) based oscillators, regardless of whether they are single-ended or differential. By using Taylor series expansion, this paper shows that second-order nonlinearity of the MOSFET will cause a shift in the DC biasing of an AI-based oscillator, depending on oscillation amplitude. The DC bias shift results in a change of the transistor transconductance and parasitic components from their original value, which will affect the oscillator resonance frequency. This explains why a small-signal S-parameter simulation is not sufficient to accurately predict the oscillation frequency and tuning range of AI-based oscillators, even at moderate oscillation amplitudes.